Comparison of different RSA variants. (17th May 2019) - Verma, Seema; Kumar, Manoj
RSA is the first public key algorithm used for encryption and decryption. Its simplicity and complexity lies in factoring a very large composite integer. It is still popular even after 39 years of its origin. In this long journey, RSA is studied many times and many security loopholes are found. To remove the loop holes researchers designed many variants of RSA. The work shows the study of different RSA variants which are popular in literature. This study includes the analysis in terms of performance and security of different RSA variants.